Transtornos mentais comuns e fatores associados em mulheres trabalhadoras de turno do sul do Brasil - Lucca, Jessica Kraemer (Universidade do Vale do Rio dos Sinos, 2022)
The aim of this study was to identify the prevalence of common mental disorders (CMD) and associated factors in female shift workers. This study belongs to a larger project entitled: “Quality and sleep deprivation and abdominal obesity in female shift workers in an industry in southern Brazil”. A cross-sectional observational study was carried out with female shift workers in an industry in southern Brazil. CMDs were assessed using the Self-Reporting Questionnaire (SRQ20), using the cutoff point of 8 points or more. Other sociodemographic, occupational, behavioral, morbidity and self-rated health variables were assessed using a questionnaire. To verify the association of independent variables with the outcome, the chi-square test was used. To estimate the Prevalence Ratios, crude and adjusted, Poisson regression with robust variance was performed. The variables were included in the analysis according to a conceptual model defined a priori that considers the existence of a hierarchy between the variables in determining the outcome. The prevalence of CMD was 47.3% (95% CI: 42.6-52.1). After adjusting for confounding factors, it was observed that black/brown women, workers with poor sleep quality and with fair/poor self-perception of health were more likely to have CMD. There was no statistically significant association between CMD and the night shift. In conclusion, the race/skin color relationship seems to overlap with the other sociodemographic variables in the occurrence of CMD. In addition, the results point to a strong relationship between poor sleep quality and CMD. It is suggested that future studies compare the relationship of CMD between shift workers and regulartime workers.
Keywords: Transtornos mentais comuns; Mulheres; Trabalho em turno; Trabalho noturno; Estudo transversal; Common mental disorders; Women; Shift work; Night work; Cross-sectional study; ACCNPQ::Ciências da Saúde::Saúde Coletiva